Contemplating Chinese Foreign Policy: Approaches to the Use of Historical Analysis1. (4th August 2013) - Blanchard, Jean‐Marc F.; Lin, Kun‐Chin
Abstract : Many have contemplated Chinese foreign policy and its future direction, but few have queried how Chinese history might illuminate both. This is unfortunate since researchers have shown that history can influence foreign policy agendas, discourses, and national goals. Moreover, it provides an invaluable tool for comparative analysis. The purpose of this introduction is to provide historical background to the articles comprising this special issue, whose contributors employ historical analysis, with the period preceding and following the Xinhai Revolution as a basis, to illuminate contemporary Chinese foreign policy – e.g., China's interest in remaking the international order and its security norms – or to suggest differences between past and present – for example, in regards to China's Asia–Pacific posture. This introduction also hopes to stimulate further work on Chinese history and foreign policy by highlighting similarities and differences between past and present with respect to, inter alia, pressures against China's territorial integrity, sovereignty, and independence, the penetration of foreign actors and ideas into China, and domestic factors limiting China's efforts to filter external influences and to respond to them.